Nilai - Nilai Pancasila dalam Pembaruan Hukum Perkawinan - Nila Amania (Pusat Riset dan Inovasi Nasional, 2025)
Pancasila has been established as both a rechtsidee (legal ideal) and a grundnorm (fundamental norm). The values of Pancasila must guide and be embodied in legal reform in Indonesia whether at the substantive level (legal content), structural level (legal institutions), or cultural level (legal culture). These values must be embedded in the Constitution of the Republic of Indonesia and further reflected in all subsequent laws and regulations. The value of national unity contained in Pancasila is reflected in the enactment of Law No. 1 of 1974 on Marriage. The unification of marriage law through this legislation abolished the diverse marriage laws that existed prior to its enactment. The value of social justice for all Indonesian people is reflected in the enactment of Law No. 16 of 2019, which amended Law No. 1 of 1974 on Marriage. The amendment, which revised the minimum age for marriage, provides justice for both men and women regarding the legal validity of marriage in Indonesia.